Attracting Native Bees to Your Florida Landscape - Rachel Mallinger; Anne Yasalonis; Gary Knox; Wayne Hobbs (EDIS, 2019)
Florida is home to approximately 315 species of native wild bees. These bees rely on flowers for survival; their diets consist exclusively of pollen and nectar harvested from flowers. Recently reported declines in some bee species have heightened awareness of bee conservation across the United States and motivated efforts to increase floral resources for bees. This 7-page fact sheet written by Rachel E. Mallinger, Wayne Hobbs, Anne Yasalonis, and Gary Knox and published by the UF/IFAS Entomology and Nematology Department shows how gardeners and land managers can aid in conservation efforts by planting flowers for bees in home or community gardens. http://edis.ifas.ufl.edu/IN1255